Unmet needs of family caregivers of hospitalized older adults preparing for discharge home. (June 2020) - McCusker, Jane; Yaffe, Mark; Lambert, Sylvie D; Cole, Martin; de Raad, Manon; Belzile, Eric; Ciampi, Antonio; Amir, Ella; Hidalgo, Marcela
Objectives: To describe unmet needs of caregivers of hospitalized older adults during the transition from hospital back home, and identify subgroups with different needs. Methods: Patients and family caregivers were recruited from an acute care hospital in Montreal, Canada. Measures included Instrumental Activities of Daily Living (IADL), Hospital Anxiety and Depression Scale (HADS), Zarit burden scale, and Family Inventory of Needs. Dimensions of unmet needs were explored with principal component analysis; regression tree models were used to identify subgroups with different unmet needs. Results: A total of 146 patient-caregiver dyads were recruited. Three categories of caregiver unmet needs were identified: patient medical information; role clarity and support; and reassurance. Caregiver subgroups with highest unmet needs were those with high burden of care plus depressive symptoms ( n  = 46) and those caring for patients with low IADL scores ( n  = 10). Discussion: Caregivers with high burden and depression are those with the greatest unmet needs during the care transition.